Cooking Recipe as a Determinant of Glycemic Index Variation in Commercial and Natural Wheat Flour: Cooking recipe and glycemic index values in commercial and natural wheat flour (Journal of the Bangladesh Agricultural University, 2024)
An in vivo study was conducted with various cooking recipes to select suitable wheat flour in view point of glycemic index (GI) value from the commercially available whole and plain wheat flour by comparing with natural wheat flour. We assessed the glycemic responses of 10 healthy individuals with reference food (50 g glucose) and cooked wheat roti, equivalent to 50 g carbohydrate, in hot (100°C) and normal water (25°C) recipes. To prevent residual effects, the individuals were kept overnight fasting throughout the study period. Capillary glucose levels at 0, 15, 30, 45, 60, 90 and 120 minutes after consuming the meals were assessed and used to determine the Incremental Area Under Curve (IAUC). Results showed a significant decrease (p